Living carriers in the East Chinese cargadores in nineteenth-century Manila - Galang, Jely A. (Philippine studies : historical and ethnographic viewpoints)
"Although the history of the Chinese in the Philippines is generally well known, what has not been probed is the way working-class Chinese lived and conducted their trades and restrictive colonial policies. Using previously unexplored archival materials, this article examines the lives and circumstances of Chinese cargadores (stevedores and transporters) within the urban and commercial milieus of Manila during the nineteenth century. Chinese cargadores were regarded as highly dependable workers, but were treated, because of their ethnicity and numerical strength, as both marginal and dangerous, needing to be strictly regulated and disciplined by the Spanish colonial state."